Tissue Composition of Agave americana L. Yields Greater Carbohydrates From Enzymatic Hydrolysis Than Advanced Bioenergy Crops - Jones, Alexander M.; Zhou, Yadi; Held, Michael A.; Davis, Sarah C. (Frontiers in Plant Science, 2020)
Agave americana L. is a highly productive, drought-tolerant species being investigated as a feedstock for biofuel production. Agave spp. and other species with Crassulacean Acid Metabolism (CAM) produce yields in semi-arid conditions that are comparable to C3 and C4 crops grown in areas with high rainfall. This study evaluates the bioethanol yield potential of A. americana by (1) examining the relationship between water use efficiency (WUE) and plant carbohydrates, (2) quantifying the carbohydrate and energy content of the plant tissue, and (3) comparing the products of enzymatic hydrolysis to that of other candidate feedstocks (Miscanthus x giganteus Greef et Deuter, Sorghum bicolor (L.) Moench, and Panicum virgatum L.). Results indicate that (1) WUE does not significantly affect soluble and insoluble (i.e. structural) carbohydrate composition per unit mass in A. americana; (2) without pretreatment, A. americana biomass had the lowest gross heat of combustion, or higher heating/calorific value, compared to high yielding C4 crops; and (3) after separation of soluble carbohydrates, A. americana cellulosic biomass was most easily hydrolyzed by enzymes with greater sugar yield per unit mass compared to the other biomass feedstocks. These results indicate that A. americana can produce substantial yields of soluble carbohydrates with minimal water inputs required for cultivation, and fiber portions of the crop can be readily deconstructed by cellulolytic enzymes for subsequent biochemical fermentation.